حلّ نكاح نساء أهل الكتاب (في ضوء القرآن الكريم) - Dr.Ume Farwa; Dr.Zainab Sadiq; Shafia Jamil (jihat-ul-islam, 2022)
Ahle-kitab is Arabic word which refers to people of the book or people who were given previous scriptures by Almighty God. The general understanding about ahle-kitab is that it refers to Jews and Christians. This article discusses marriage with women of Ahl e Kitab. There are two groups in this regard. A complete discussion in the light of their arguments is given in the articleAccording to oe group it is completely forbidden to marry a kitabi woman. Whereas according to the other group marrying a Kitabi woman is permissible and there are certain conditions that should be present for the validity of marriage.